The Role of the Community and Health Workers in Preventing Stunting in Tuapeijat Village, Mentawai Province - Asnur, Lise; Sahara, Siti; Sukardi, Tega; Effendi, M Abdurrahman; Fadila, Lidia Ramatul; Delviyanti, Diva Tri (Universitas Pahlawan Tuanku Tambusai, 2025)
This article presents a qualitative analysis of the collaborative roles between the community and health workers in stunting prevention efforts within Tuapeijat Village, Mentawai Islands, a region confronting significant geographical challenges and limited healthcare facilities. Through interviews with key informants (parents, Posyandu cadres, midwives, and health center staff), the study found that the community actively participates in Posyandu and nutrition counseling, although effectiveness is constrained by limited knowledge and access to nutritional resources. Meanwhile, health workers function as facilitators and educators by monitoring child growth and providing interventions, but are hindered by constraints in personnel and facilities. Therefore, the success of stunting prevention highly depends on a strong synergy between these two parties, implemented through culturally appropriate approaches, thus emphasizing the need to focus on community empowerment and capacity building of health workers to foster a healthier future generation.